Glycerolysis of methyl oleate on MgO: experimental and theoretical study of the reaction selectivity - Belelli, Patricia Gabriela (2015)
The liquid-phase MgO-promoted glycerolysis of methyl oleate, a fatty acid methyl ester (FAME), to give acylglycerol products was studied both, experimentally and by density functional theory (DFT). Catalytic results showed that strongly basic low coordination O2− surface sites participate in kinetically relevant steps of the glycerolysis reaction. Changes in the selectivity toward the different mono- and diglyceride isomers were investigated by varying the reaction conditions. The main product was always α-glyceryl monooleate (α-MG), a monoglyceride with the ester fragment at one of the terminal positions of the glycerol molecule; the β-MG isomer, with the ester substituted at position 2 was obtained in much lower amounts. The molecular modeling of glycerol (Gly) and FAME adsorptions as well as of the glycerolysis reaction was carried out using periodic DFT calculations and a model of stepped MgO surface. Results indicated that FAME was more weakly adsorbed than Gly; the latter adsorbs on a coordinatively unsaturated surface O2− site with Osingle bondH bond breaking at position 2 of the Gly molecule, giving therefore a surface β-glyceroxide species. Calculations explained the apparent contradiction between the preferential formation of the α-MG isomer and the energetically favored dissociation of the secondary OH group of Gly that leads to the β-glyceroxide species. They predict that the β-glyceroxide species participates in the pathways conducting to both, α- and β-MG isomers. Synthesis of α-MG occurs by Csingle bondO coupling of β-glyceroxide with FAME at one of the two primary OH groups of the β-glyceroxide species. Two transition states (TS) and a tetrahedral intermediate (TI) are involved in both, α-MG and β-MG isomer formation. However, the pathway toward β-MG is limited by the large sterical effects associated to the TI formation. Contrarily, the TI leading to α-MG is relatively easy to form.